A newly discovered biodiversity hotspot of many-plumed moths in the Mount Cameroon area: first report on species diversity, with description of nine new species (Lepidoptera, Alucitidae) - Ustjuzhanin, Peter (Zookeys, 2018)
Abstract. Fifteen species of many-plumed moths are recorded from the Mount Cameroon area, SW Cameroon, West Africa. Nine species: Alucitalongipenis Ustjuzhanin & Kovtunovich, sp. n., A.lidiya Ustjuzhanin & Kovtunovich, sp. n., A.ludmila Ustjuzhanin & Kovtunovich, sp. n., A.escobari Ustjuzhanin & Kovtunovich, sp. n., A.mischenini Ustjuzhanin & Kovtunovich, sp. n., A.fokami Ustjuzhanin & Kovtunovich, sp. n., A.janeceki Ustjuzhanin & Kovtunovich, sp. n., A.besongi Ustjuzhanin & Kovtunovich, sp. n., and A.olga Ustjuzhanin & Kovtunovich, sp. n., are described as new for science. Four species are recorded as new from Cameroon: A.acalyptra, A.chloracta, A.coffeina, and A.spicifera. By these records, the Mount Cameroon area has become the richest known Afrotropical locality for the Alucitidae, highlighting its tremendous value for biodiversity conservation.